Evaluation of mineral trioxide aggregate and calcium hydroxide cement as pulp-capping agents in human teeth - Accorinte, Maria de Lourdes R.; Holland, Roberto [UNESP]; Reis, Alessandra; Bortoluzzi, Marcelo C.; Murata, Sueli S. [UNESP]; Dezan Junior, Eloi [UNESP]; Souza, Valdir de [UNESP]; Alessandro, Loguercio Dourado (Elsevier B.V., 2008)
This study evaluated the histomorphologic response of human dental pulps capped with mineral trioxide aggregate (MTA) and Ca(OH)(2) cement (CH). Pulp exposures were performed on the occlusal floor of 40 human permanent premolars. After that, the pulp was capped either with CH or MTA and restored with composite resin. After 30 and 60 days, teeth were extracted and processed for histologic exam and categorized in a histologic score system. The data were subjected to Kruskal-Wallis and Conover tests (alpha = .05). All groups performed well in terms of hard tissue bridge formation, inflammatory response, and other pulpal findings. However, a lower response of CH30 was observed for the dentin bridge formation, when compared with MTA30 and MTA60 groups. Although the pulp healing with calcium hydroxide was slower than that of MTA, both materials were successful for pulp capping in human teeth.
Keywords: biocompatibility; calcium hydroxide; human pulp; mineral trioxide aggregate; pulp capping; pulp therapy